2011
DOI: 10.1002/uog.8861
|View full text |Cite
|
Sign up to set email alerts
|

Absent gallbladder on fetal ultrasound: prenatal findings and postnatal outcome

Abstract: Objectives Fetal gallbladder non-visualization on prenatal ultrasound in the second trimester is uncommon and in most cases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 26 publications
2
35
0
2
Order By: Relevance
“…These findings concur with those of Dreux et al [6] who concluded that prior to 22 weeks of gestation, an abnormal pattern of amniotic fluid digestive enzymes had 90% sensitivity and 80% specificity in detecting CF or BA; however, after 22 weeks, the sensitivity dropped to 53%. In contrast, Shen et al [7] concluded that testing digestive enzymes in amniotic fluid is not justified for assessing cases of isolated NVFGB. However, their study included 21 fetuses with NVFGB, in which GGTP was found to be normal in all 5 cases in which it was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings concur with those of Dreux et al [6] who concluded that prior to 22 weeks of gestation, an abnormal pattern of amniotic fluid digestive enzymes had 90% sensitivity and 80% specificity in detecting CF or BA; however, after 22 weeks, the sensitivity dropped to 53%. In contrast, Shen et al [7] concluded that testing digestive enzymes in amniotic fluid is not justified for assessing cases of isolated NVFGB. However, their study included 21 fetuses with NVFGB, in which GGTP was found to be normal in all 5 cases in which it was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversy exists regarding the yield of assessing GGTP levels of amniotic fluid in the prenatal diagnosis of fetuses whose gallbladder cannot be visualized [6,7,18,19,20]. This is mainly due to the rarity of BA, with a reported incidence of 1:20,000 live births [9], and the scarcity of reports on the prenatal diagnosis of BA.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is a well‐described postnatal entity 2 associating biliary atresia and a portal cyst. Nonvisualization of the gallbladder during the second trimester ultrasound should prompt concern for BA 3, 4, 5. Other gallbladder abnormalities can be diagnosed prenatally such as agenesis, left‐sided, septated or bilobed gallbladder 6.…”
mentioning
confidence: 99%